Public-private partnership (PPP): history in Brazil and its insertion in Brazilian educational policy - Danielly Cristinne Barbosa de Campos; Alberto Damasceno (Universidade Federal de Santa Catarina, 2020)
This paper aims to analyze public-private partnership (PPP) historical trajectory in Brazil, the process of regulation and consolidation of PPPs in a Brazilian political scene, as well as how such partnerships are part of the context of  Basic Education in said country. The analysis departs from a historical study on PPPs, going through a discussion about the reconfiguration of the State role from 90's onwards. Results reveal that these partnerships have occurred in Brazil since D. Pedro II's management, based on premises of improving public services; also that the discourse has become more sophisticated over time, due to such discourses being employed in the same way to solve old issues of public responsibility, as it is with education. Furthermore, through PPPs, activities carried out in Basic Education have been planned, done and assessed by the private sector, which proposes as its own attributes aspects as efficacy, efficiency and ability to improve both the condition and indices of Brazilian education, although it also changes the meaning of an education for a fully realized citizenship to that of a collective work towards high indicators.